2022
DOI: 10.3390/cancers14246048
|View full text |Cite
|
Sign up to set email alerts
|

ARDS after Pneumonectomy: How to Prevent It? Development of a Nomogram to Predict the Risk of ARDS after Pneumonectomy for Lung Cancer

Abstract: (1) Background: The cause of ARDS after pneumonectomy is still unclear, and the study of risk factors is a subject of debate. (2) Methods: We reviewed a large panel of pre-, peri- and postoperative data of 211 patients who underwent pneumonectomy during the period 2014–2021. Univariable and multivariable logistic regression was used to quantify the association between preoperative parameters and the risk of developing ARDS, in addition to odds ratios and their respective 95% confidence intervals. A backward st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Maret et al have already identified ASA > 2 as an independent factor for major cardiopulmonary complications and mortality after pneumonectomy [4]. In addition, Mazella et al identified ASA score as an independent factor for ARDS after pneumonectomy [29]. Similarly, in our study, the ASA score, particularly for patients with an ASA score of 4, was an independent score for mortality.…”
Section: Discussionsupporting
confidence: 84%
“…Maret et al have already identified ASA > 2 as an independent factor for major cardiopulmonary complications and mortality after pneumonectomy [4]. In addition, Mazella et al identified ASA score as an independent factor for ARDS after pneumonectomy [29]. Similarly, in our study, the ASA score, particularly for patients with an ASA score of 4, was an independent score for mortality.…”
Section: Discussionsupporting
confidence: 84%